Safety of patients with mental disorders: a collective construction of strategies - Fernanda Cordeiro Sirtoli Vantil; Eliane de Fátima Almeida Lima; Karla Crozeta Figueiredo; Leila Massaroni; Ana Inês Sousa; Cândida Caniçali Primo
ABSTRACT Objective: to describe risk management implementation in the safety of patients with mental disorders through action research. Method: an action research carried out with a multidisciplinary team from a reference hospital in mental health in Southeast Brazil. Results: three strategies considered as managerial technologies for the mentally ill patient were developed: risk management diagram for patient safety; patient safety protocols; and textual proposal of software for internal management of incident notifications. Final considerations: this action research allowed a collective discussion by the whole multidisciplinary team, enabling strategy drafting for risk management implementation and improvement of care quality in the safety of patients with mental disorders at the study site.